2019
DOI: 10.3390/ph12030123
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling Hepcidin Plasma Protein Binding: Evidence from Peritoneal Equilibration Testing

Abstract: Peptide hormone hepcidin regulates systemic iron metabolism and has been described to be partially bound to α2-macroglobulin and albumin in blood. However, the reported degree of hepcidin protein binding varies between <3% and ≈89%. Since protein-binding may influence hormone function and quantification, better insight into the degree of hepcidin protein binding is essential to fully understand the biological behavior of hepcidin and interpretation of its measurement in patients. Here, we used peritoneal di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…One is efficient filtration of hepcidin as a small peptide through the renal glomerular membrane [ 27 ], followed by reuptake and degradation of filtered hepcidin in the proximal tubule, utilizing a generic mechanism for recycling the amino acid content of filtered proteins. Efficient filtration of hepcidin in the glomerulus is facilitated by the relatively low fraction of hepcidin that is bound by plasma protein, estimated at about 40% [ 28 ]. A small percentage of filtered hepcidin survives the uptake and degradation in the proximal tubule and can be detected in urine, similarly to other peptide hormones.…”
Section: Hepcidin Synthesis and Eliminationmentioning
confidence: 99%
“…One is efficient filtration of hepcidin as a small peptide through the renal glomerular membrane [ 27 ], followed by reuptake and degradation of filtered hepcidin in the proximal tubule, utilizing a generic mechanism for recycling the amino acid content of filtered proteins. Efficient filtration of hepcidin in the glomerulus is facilitated by the relatively low fraction of hepcidin that is bound by plasma protein, estimated at about 40% [ 28 ]. A small percentage of filtered hepcidin survives the uptake and degradation in the proximal tubule and can be detected in urine, similarly to other peptide hormones.…”
Section: Hepcidin Synthesis and Eliminationmentioning
confidence: 99%
“…PD is a continuous technique with diffusive and convective transport of small-and middle-molecular solutes; however, individual properties of peritoneal membrane may influence efficacy of hepcidin removal. So far, peritoneal hepcidin clearance using peritoneal equilibration test was evaluated only in one small study (36). The efficacy of PD removal should be confirmed in further studies.…”
Section: Hepcidin In Chronic Kidney Diseasementioning
confidence: 99%
“…Fifty percent of critically ill patients develop AKI and 25% require RRT [ 3 ]. Hepcidin and pro-hepcidin have molecular weights of 2700 Da and 10,000 Da, respectively, and, therefore, may be removed by continuous RRT (CRRT), which uses membranes with a cut-off of 35,000 Da [ 4 ]. The protein-bound fraction of hepcidin is about 40% [ 4 ] which does not impede its elimination by convection or diffusion [ 5 ].…”
mentioning
confidence: 99%
“…Hepcidin and pro-hepcidin have molecular weights of 2700 Da and 10,000 Da, respectively, and, therefore, may be removed by continuous RRT (CRRT), which uses membranes with a cut-off of 35,000 Da [ 4 ]. The protein-bound fraction of hepcidin is about 40% [ 4 ] which does not impede its elimination by convection or diffusion [ 5 ]. It has been demonstrated that maintenance dialysis with both super-flux polysulphone (PS) and acrylonitrile 69 (AN69) membranes similarly removed hepcidin [ 5 ].…”
mentioning
confidence: 99%